Dar Al-Salam Dan Dar Al-Kuffar Dalam Konsepsi Hubungan Antar Negara - Mawardi Mawardi (Millah: Journal of Religious Studies, 2002)
The goal of this article is to disclose the principle toward the connection between Dar al-Salaam and Dar al-Kuffar according to fiqh siasah perspective. The connection seems like living together side by side peacefully between two countries or more which have different political viewpoint. The fundamental principle in Islam says that Moslem are not allowed to slay other person whohas different religion accept if they attack or to slow Moslemin telling the spirit. The war is only allowedin order to protect missionary from the overlimit rebellious. The peaceful application in Islam happens in an agreement. Peace agreement is formally accepted if it involves three points, which are all the sides who has full right from his country, agree to do it, and not taking over side in Islamic law principle. Other than of the peaceagreement according to fiqh siasah perspective that rule about extradition, politically conservatory, and diplomatic relation between two countries. Take the real example from all of it shown that Hudaibiya agreement betweenMoslems led by Rasulullah peace be upon him and musyrik people led by suhail bin Amr.